2018
DOI: 10.5219/887
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of pumpkin powder in baked rolls

Abstract: Bakery products are good vehicles for dietary fiber incorporation. Traditionally, the source of dietary fiber has been mainly from cereals. However, vegetable can be used as potential source of dietary fiber. Pumpkin powder was characterized with good hydration properties (water holding and water retention capacity and swelling capacity), but fat absorption capacity was very low. Wheat flour was substituted with pumpkin powder at different level (2.5; 5; 7.5; and 10%). Addition of pumpkin powder modified the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Water absorption of dough is the amount of water required to make the dough of proper consistency for bread baking (Minarovičová et al., 2018). As shown in Table 2, as the pumpkin powder content was elevated, the dough water absorption was reduced.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Water absorption of dough is the amount of water required to make the dough of proper consistency for bread baking (Minarovičová et al., 2018). As shown in Table 2, as the pumpkin powder content was elevated, the dough water absorption was reduced.…”
Section: Resultsmentioning
confidence: 99%
“…From our results, it was concluded that the addition of pumpkin powder increased the dough development time. This change could have been due to the differences in the physiochemical properties of the constituents of the pumpkin powder and wheat flour (Minarovičová et al., 2018). Dough stability indicates the strength and resistance of dough (Minarovičová et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations